Comparison of the Dominance of Internal and External Influences on the Return of Shares of Companies Listed in IDX30 - Hutama Sanputra Arifin; Tri Ramaraya Koroy; Gemi Ruwanti; Zainal Arifin (STKIP Singkawang, 2021)
This study aims to determine the comparison of external and internal influences on stock returns on the Indonesia Stock Exchange. The research method uses quantitative methods from secondary data of financial analysis on 16 companies from 30 companies on the IDX Index that have a high level of liquidity and have a large capitalization selected by the IDX (Indonesia Stock Exchange) with several selection criteria, the selection is carried out by the IDX regularly 2 times every year, namely in February and August. from 2014-2018 and data from Bank Indonesia on economic growth and inflation in the same year. The data analysis technique used multiple regression. The results show that the influence of external factors in the form of economic growth and inflation is more dominant than the company's internal factors in the form of DY (Dividend Yield), EPS (Earning Per Share), ROE (Return On Equity), PER (Price Earning Ratio) affect stock returns. Implementation for companies that go public needs to pay attention to the dynamics of environmental changes, especially the inflation rate which can cause investors to sell their shares, while this phenomenon is an opportunity for some investors to get a cheaper share price than many other investors have released.